An econometric study of the effect of interest rates on inflation rates in Algeria 1980-2018; using the ARDL model - Amel Touer; Mokhtari Abdeljabar (Dirassat Journal Economic Issue, 2021)
This study aimed to find out the extent of the impact of interest rates on inflation in Algeria during the period 1980-2018, and this study has divided into two aspects a theoretical aspect that includes some theoretical basics for both interest rates and inflation rates. Ardl, using eviews.10, and after studying the stability of both variables, the results showed a long-term equilibrium relationship between interest rates and inflation rates in Algeria, and the study also found that interest rates affect inflation adversely in Algeria, in the long and short term, i.e. The lower the interest rates, the higher the inflation rate in Algeria